Kegiatan Marketing Pr Label Musik Digital Audio Tape Bandung - M Fadil Ramadhan; M. Subur Drajat (Jurnal Riset Public Relations, 2021)
Abstract. Music labels Digital Audio Tape having the marketing public relations that his services can be used by audience. The marketing public relations label was set up by Trizha Harun as public relations at the music labels Digital Audio Tape. ( ruslan 2008: 249 ), Public relations serves to communicate both sides between the company with public internal and external relationships and mutual with the audience be considered important by label. Activity public relations is held mutual communication between institution with public intended to create mutual understanding and support for the achievement of a a particular purpose, policy, production activities the progress of institution or a positive image of institutions concerned. The public function of relations at the labels music Digital Audio Tape to increase the consumers which will perform recording on music label Digital Audio Tape. The purpose of this research that is to know the marketing public relations done by music labels Digital Audio Tape. The methodology qualitative perspective case study by Robert K. Yin more trying to map technique single case analysis in the analysis the marketing public relations done by music labels Digital Audio Tape. The research music label the concept of representatives using three with the creation event showcase cover tune in instagram, created an impromptu event or shocking venues, combining vocal technique of various genre of music becomes hip hop. Abstrak. Label music Digital Audio Tape memiliki kegiatan marketing Public Relations agar jasanya dapat digunakan oleh khalayak. Kegiatan marketing Public Relations label tersebut dibuat oleh Trizha Harun selaku Public Relations pada label musik Digital Audio Tape. (Ruslan 2008 :249), Public Relations berfungsi untuk menjalin komunikasi dua arah antara perusahaan dengan publik internal dan eksternal serta membina hubungan yang saling menguntungkan dengan khalayak atau pihak yang dianggap penting oleh label. Aktivitas Public Relations adalah menyelenggarakan komunikasi timbal balik antara lembaga dengan publik yang bertujuan untuk menciptakan saling pengertian dan dukungan bagi tercapainya suatu tujuan tertentu, kebijakan, kegiatan produksi demi kemajuan lembaga atau citra positif lembaga bersangkutan. Fungsi Public Relations pada label musik Digital Audio Tape untuk meningkatkan pelaku konsumen yang akan melakukan rekaman di label musik Digital Audio Tape. Tujuan penelitian ini yaitu untuk mengetahui kegiatan marketing public relations yang dilakukan oleh label musik Digital Audio Tape. Metode penelitian kualitatif dengan perspektif studi kasus Robert K. Yin yang lebih berupaya memetakan teknik single case analysis pada analisis kegiatan marketing public relations yang dilakukan oleh label musik Digital Audio Tape. Dari hasil penelitian label musik menggunakan tiga konsep MPR dengan cara menciptakan event showcase cover lagu di instagram, menciptakan mengadakan event dadakan atau (shocking venue), menggabungkan teknik vocal dari berbagai genre musik menjadi hip hop.